2009
DOI: 10.1634/stemcells.2008-0433
|View full text |Cite
|
Sign up to set email alerts
|

Derivation and Characterization of Canine Embryonic Stem Cell Lines with In Vitro and In Vivo Differentiation Potential

Abstract: ABSTRACT

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(67 citation statements)
references
References 81 publications
(96 reference statements)
6
60
0
1
Order By: Relevance
“…Cells derived from plated EBs on day 20 postdifferentiation were analyzed and found to be positive for the presence of cell derivatives from the 3 germ layers, including b-III neuron-specific tubulin (TUJ1) for the ectoderm, vimentin for the mesoderm, and alpha-fetoprotein (AFP) for the endoderm (Fig. 4B) [5,33]. Using qRT-PCR, we also found that differentiated ciPSCs silenced the canine OCT4 and NANOG (P < 0.05; Fig.…”
Section: In Vitro Differentiationmentioning
confidence: 84%
See 1 more Smart Citation
“…Cells derived from plated EBs on day 20 postdifferentiation were analyzed and found to be positive for the presence of cell derivatives from the 3 germ layers, including b-III neuron-specific tubulin (TUJ1) for the ectoderm, vimentin for the mesoderm, and alpha-fetoprotein (AFP) for the endoderm (Fig. 4B) [5,33]. Using qRT-PCR, we also found that differentiated ciPSCs silenced the canine OCT4 and NANOG (P < 0.05; Fig.…”
Section: In Vitro Differentiationmentioning
confidence: 84%
“…Approximately 58% of dog genetic diseases resemble the specific human diseases caused by mutations in the same gene [17,18]. Also, dogs share a variety of biochemical and physiological characteristics with humans; their physiologies, disease presentations, and clinical responses often parallel those of humans better than do those of their rodent counterparts [5,17]. This underscores the dog's importance as a reliable preclinical model for testing the feasibility of regenerative medicine and tissue engineering approaches to treat its own diseases and those of man.…”
Section: Introductionmentioning
confidence: 99%
“…Since then, induced pluripotent stem cells (iPSCs) or iPSC-like cells have been derived from different species, including human [11], rhesus monkey [12], rat [13], pig [14,15], dog [16,17], rabbit [18], marmoset [19], sheep [20][21][22], and more recently, horse [23] and cow [24]. Transgene-mediated reprogramming offers distinct technical advantages over other established reprogramming techniques, and the resulting cell lines are functionally comparable to ESCs [25].…”
Section: Introductionmentioning
confidence: 99%
“…However, the used technology still needs optimization as they undergo spontaneous differentiation over long-term culture, irrespective of the source of derivation, that is, in vivo or in vitro produced blastocysts. Canine ESCs have also been isolated from pre-implantation stage embryos with both in vitro and in vivo differentiation potential (Hatoya et al 2006;Hayes et al 2008;Schneider et al 2008;Vaags et al 2009;Wilcox et al 2009;Schneider et al 2010). These canine ESCs were able to undergo self-renewal for prolonged periods of culture while remaining undifferentiated, and expressed a characteristic pluripotency gene expression profile, such as OCT4, SSEA3 and SOX2.…”
Section: Embryonic Stem Cells In Domestic Animalsmentioning
confidence: 99%